Stress-state modeling in the vicinity of an optical fiber embedded Into polymer composite material taking into account the structural features of the composite - Kosheleva, Natalia Aleksandrovna; Serovaev, Grigorii Sergeevich (Computational Continuum Mechanics, 2017)
The present work is a fragment of two important scientific areas: mechanics of polymeric composite materials (PCM) and creation of new diagnostic tools and monitoring of the mechanical state of a structure based on the use of fiber-optic sensors. The nomenclature and the range of their applications expand very quickly. Currently, the percentage of composite materials is one of the indicators of respective products competitiveness indices. At the same time, theoretical developments that provide an assessment of the performance of PCM products, do not always meet designers requests on new products. Therefore, the model estimates should be supplemented with modern monitoring systems. Fiber-optic sensors offer opportunities for creating new monitoring scenarios. One of them is connected with the use of embedded sensors into PCM. In this case, a new kind of smart material appears, in which the PCM, along with the basic functions, provides information on its parameters: temperature, strain, etc. The creation of this class of smart materials requires the solution a number of tasks. Present work is devoted to the evaluation by mathematical modeling methods of changes in the stiffness and strength characteristics of PCM products due to optical fiber sensors embedding into material. In contrast to the known works, in computational models constructing, the following are taken into account: the layered structure of PCM; options for stacking layers; layers and optical fiber layout options; the presence of a technological defect in the form of a resin pocket with the elimination in the model of points of stress singularity that are present in known design schemes. The result of the work is the use of the proposed model for estimating the level of stress concentration in the layers of composite material adjacent to the optical fiber.
Keywords: composite materials; optical fibers; stress-strain state; numerical simulation